1996
DOI: 10.1143/jjap.35.39
|View full text |Cite
|
Sign up to set email alerts
|

Pt/PZT/n-SrTiO3 Ferroelectric Memory Diode

Abstract: We fabricated a new nonvolatile ferroelectric memory, which consists of vertical metal-ferroelectric- semiconductor diodes. Our diode has a simpler structure than an Ferroelectric Random Access Memory (FRAM) cell, and operates at a lower voltage than Metal Ferroelectric Semiconductor Field Effect Transistors (MFS-FETs) or conventional flash memories. We demonstrated the memory operation using a Pt/PZT/n- SrTiO3 diode in this work. We deposited (001)-oriented PZT on (100) 0.5 wt% Nb doped n-type Sr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…[20][21][22][23][24][25][26][27][28] In the case of ferroelectrics, the issue is further complicated by characteristics such as interface properties, i.e., the barrier height and the sign of the remnant charge of the ferroelectric material. [20][21][22][23]27,28 Nonetheless, from I-V characteristics alone it might be a risky task to conclude the nature of the underlying mechanism. 19,26,28,30 Therefore, it is critical to be able to distinguish a ferroelectric switching from that of a nonferroelectric origin, and this forms the motivation for this letter.…”
Section: Methods To Distinguish Ferroelectric From Nonferroelectric Ormentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28] In the case of ferroelectrics, the issue is further complicated by characteristics such as interface properties, i.e., the barrier height and the sign of the remnant charge of the ferroelectric material. [20][21][22][23]27,28 Nonetheless, from I-V characteristics alone it might be a risky task to conclude the nature of the underlying mechanism. 19,26,28,30 Therefore, it is critical to be able to distinguish a ferroelectric switching from that of a nonferroelectric origin, and this forms the motivation for this letter.…”
Section: Methods To Distinguish Ferroelectric From Nonferroelectric Ormentioning
confidence: 99%
“…Thus, they not only experimentally demonstrated the RS behavior in ferroelectric diodes but also inferred that the RS behavior in ferroelectric heterostructures is polarization dependent. Subsequently, the RS behaviors in BaTiO 3 /Nb:SrTiO 3 , BiFeO 3 /SrRuO 3 , (PbLa)(ZrTi)O 3 /LaNiO 3 , and other ferroelectric heterostructures were also reported, and the possible mechanisms were discussed . Using p‐type semiconductor (PbLa)(ZrTi)O 3 as a ferroelectric layer and p‐type semiconductors (LaSr) 2 CuO 4 or LaNiO 3 or n‐type semiconductors (NdCe) 2 CuO 4 or Sr(TiNb)O 3 as a substrate electrode, p–p and p–n ferroelectric heterojunctions were fabricated.…”
Section: Mechanisms Of Rs Behavior In Ferroelectric Heterostructuresmentioning
confidence: 99%
“…Using p‐type semiconductor (PbLa)(ZrTi)O 3 as a ferroelectric layer and p‐type semiconductors (LaSr) 2 CuO 4 or LaNiO 3 or n‐type semiconductors (NdCe) 2 CuO 4 or Sr(TiNb)O 3 as a substrate electrode, p–p and p–n ferroelectric heterojunctions were fabricated. [27b] The results showed that RS behavior was observed in p–n heterostructures with an ON/OFF ratio of 300 but not in p–p heterostructures. By analyzing the conduction mechanism in the p–p or p–n heterostructures, it has been suggested that the interfacial energy band structures of these heterostructures modulated by polarization switching determine the RS behavior in ferroelectric heterostructures.…”
Section: Mechanisms Of Rs Behavior In Ferroelectric Heterostructuresmentioning
confidence: 99%
“…However, the ongoing trend of miniaturization may level the technological efforts in bringing FRAM into production, since charge-based devices require a minimum area for information readout. Various concepts of resistive memories (RRAM)-e.g., based on magnetic tunnel junctions-(MRAM) [4], phase change materials (PCM, Ovonics) [5], [6], ferroelectric tunnel junctions [7], ferroelectric field-effect transistors (FerroFET) [8], [9], ferroelectric diodes [10]- [12], or charge trapping/detrapping effects [13], which do not show this disadvantage, are currently under development. The key issue of all approaches is to overcome the limitations of today's flash memories concerning low writing speed, cycling endurance, and large programming voltages.…”
Section: Introductionmentioning
confidence: 99%
“…Meyer between two ohmic contacts. The metal-ferroelectricsemiconductor-metal (MFSM) structure can be regarded as a generalization of existing ferroelectric diode concepts consisting of a one-layer structure, in which the ferroelectric layer is embedded in two metal electrodes (MFM structure) or sandwiched between a metal and a semiconductor (MFS structure) [10]- [12]. The new device combines the ferroelectric information storage principle with a lowresistive information readout.…”
Section: Introductionmentioning
confidence: 99%